Developing a UV-Curable, Environmentally Benign and Degradable Elastomer for Soft Robotics. (31st January 2018) - Rueben, Jacob; Walker, Stephanie; Huhn, Stephen; Simonsen, John; Mengüç, Yiğit
ABSTRACT: This paper introduces preliminary work on a UV-curable, environmentally benign and degradable elastomer, poly(glycerol sebacate itaconate), or PGSI, for use in soft robotics. A one-pot, solvent-free synthesis route using safe and inexpensive chemical reagents was developed to enable easy adoption into soft robotics labs. Material characterization of non-aged PGSI samples gave: ultimate tensile strength (UTS) ranging from 134 to 193 kPa with moduli ranging from 57 to 131 kPa and elongations at break ranging from 105 to 137 % (12 samples from 6 batches tested), and resilience values ranging from 73 to 82 % (3 samples from 3 batches tested). FTIR analysis showed a possible decrease in carbon-carbon double bonds after UV curing, evidencing a decrease in itaconic acid methylene groups from photoinitiated free radical cross-linking. NMR on the pre-polymer suggested incorporation of itaconic acid into the main polymer chain and evidence of heterogeneity of the polymer backbone resulting from glycerol bonding. An example molded soft pocket pneumatic actuator is created and briefly characterized. With further development, PGSI can be a degradable material to incorporate into temporary soft robots.